What drives the relevance and reputation of economics journals? An update from a survey among economists - Justus Haucap; Johannes Muck (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This is paper analyses the interrelationship between perceived journal relevance and reputation. Based on a survey of 705 members of the German Economic Association, we find a strong interrelationship between journal reputation and relevance where a journal's perceived relevance has a stronger effect on the journal's reputation than vice versa. Moreover, past journal ratings conducted by the Handelsblatt and the German Economic Association (GEA) directly affect journals' reputation among German economists and indirectly also their perceived relevance, but the effect on reputation is more than twice as large as the effect on perceived relevance. In general, citations have a non-linear impact on perceived journal reputation and relevance. While the number of landmark articles published in a journal increases reputation, an increase in the so-called H-index even tends to decrease a journal's perceived relevance, as long as this is not simultaneously reflected in a higher Handelsblatt- and/or GEA-rating. We also identify significant differences in the views on journal relevance and reputation between different age groups.
Keywords: A11; A14; I23; L82; 330; Economic Journals; Academic Journals; Reputation; Relevance; Rigor; Economists; Fractional Response Models